Slot Die Coated and Flexo Printed Highly Efficient SMOLEDs. Issue 2 (12th December 2016) - Raupp, Sebastian; Daume, Dominik; Tekoglu, Serpil; Merklein, Lisa; Lemmer, Uli; Hernandez‐Sosa, Gerardo; Sauer, Hans Martin; Dörsam, Edgar; Scharfer, Philip; Schabel, Wilhelm
Abstract : A basic solution‐processable organic light‐emitting diode (OLED) stack comprising two organic layers is presented in this study. The hole injection layer (poly(3, 4‐ethylenedioxythiophene)‐poly(styrenesulfonate), PEDOT:PSS) is slot die coated and flexographically printed for process comparison in terms of film homogeneity and the device performance. The emissive layer consisting of a small molecule host–guest system with a green triplet emitter is slot die coated. The single layer thicknesses are mapped by an in‐house developed imaging color reflectometry enabling the precise measurement of the layer thicknesses over the whole coating area (>50 cm 2 ). Luminance, current density, and light and current efficiency are defined for two different pixel sizes with the active area of 6 × 4 and 14 × 14 mm 2 . A total of 100 OLEDs are measured showing a very low standard deviation for the different pixels. The solely slot die coated OLEDs show much higher current and power efficiency than the OLEDs with flexographically printed PEDOT:PSS. Small molecule OLEDs reach efficiencies up to 30 cd A −1 and 8 lm W −1 . Additionally OLED demonstrators with an active area of ≈27 cm 2 are fabricated. Abstract : SMOLEDs are fabricated by slot die coating and flexographic printing . Two organic layers comprising poly(3, 4‐ethylenedioxythiophene)‐poly(styrenesulfonate) and a green small molecule system are cast from solution. The film homogeneity of each layer is mapped via imaging color reflectometry. Devices can be processed reproducibly and show a process dependent performance. Efficiencies up to 30 cd A −1 and 8 lm W −1 are obtained.